Transforming Junior High School Teachers' Basic STEM Knowledge through Training to Strengthen STEM-Based Mathematics Learning - Faradiba Izzati Sa'adah; Endah Budi Rahaju (Universitas Negeri Surabaya, 2026)
The implementation of STEM (Science, Technology, Engineering, and Mathematics) based mathematics learning depends on teachers’ conceptual understanding of interdisciplinary integration. Although STEM has been widely introduced through training programs, prior studies indicate that junior high school mathematics teachers’ understanding remains partial. This study aims to describe how STEM training transforms teachers’ understanding in conceptual, applicative, and affective aspects. This study used a qualitative descriptive design with a pretest–posttest approach, analyzing teachers’ responses through content analysis to identify patterns of conceptual change. The study involved 30 junior high school mathematics teachers selected through purposive sampling. Data were collected using pretest and posttest open-ended essay questions and analyzed through coding and thematic categorization. The findings revealed that before the training, most teachers perceived STEM merely as a combination of subjects, without clearly understanding how science, technology, engineering, and mathematics are integrated through problem-solving processes, design activities, and specific learning objectives. After the training, a clear shift occurred, with most teachers developing more accurate and integrated conceptions of STEM. They were able to explain STEM as an interdisciplinary approach focused on problem solving rather than subject integration alone. In practice, most teachers reached a contextual level of implementation by providing authentic examples such as real-world problem-solving activities, simple engineering design tasks, and the integration of mathematical calculations and technology. Teachers’ confidence also increased significantly, indicating greater readiness to implement STEM-based learning. These findings highlight the importance of continuous and well-designed STEM training program.